Effect of cavitation on energy conversion characteristics of a multiphase pump. (November 2021) - Shi, Guangtai; Wang, Shan; Xiao, Yexiang; Liu, Zongku; Li, Helin; Liu, Xiaobing
Abstract: To reveal the effect of cavitation on the energy conversion characteristics of helical axial multiphase pump (Abbreviated to multiphase pump), the cavitation flow in multiphase pump is simulated. The results show that with the decrease of cavitation number σ, cavitation firstly extends along the streamwise of blade suction side, and then turns to the pressure side of blade. When cavitation develops to fracture stage, the suction side of the blade is completely covered by bubbles; The vapor volume fraction in the impeller is almost 0 at the inception and critical cavitation stages; When cavitation develops to fracture stage, cavitation extends to the whole impeller passage. The output power of impeller is mainly contributed to the power done by the pressure. The power done by the viscous force in the critical fracture cavitation stage is slightly reduced. While, the power done by the pressure in the fracture cavitation stage decreases greatly. With the evolution of cavitation, the turbulence dissipation loss in the impeller decreases gradually. Moreover, in the critical fracture and fracture cavitation stages, the friction loss increases greatly compared with the previous two cavitation stages, resulting in an increment of the total energy loss. Highlights: The numerical calculation of multiphase pump is carried out by considering cavitation. The law of cavitation evolution within multiphase pump were studied. With the evolution of cavitation, the turbulent dissipation loss in the impeller decreases gradually. The blade load decreases and the output power decreases in fracture cavitation stage. The increase of the vapor volume fraction in the impeller leads to the increase of the total flow loss in the impeller.